2023
DOI: 10.1021/acs.est.3c05284
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Atmospheric Particle Phase State Using an Explainable Machine Learning Approach Based on Particle Rebound Measurements

Yanting Qiu,
Yuechen Liu,
Zhijun Wu
et al.

Abstract: The particle phase state plays a vital role in the gas− particle partitioning, multiphase reactions, ice nucleation activity, and particle growth in the atmosphere. However, the characterization of the atmospheric phase state remains challenging. Herein, based on measured aerosol chemical composition and ambient relative humidity (RH), a machine learning (ML) model with high accuracy (R 2 = 0.952) and robustness (RMSE = 0.078) was developed to predict the particle rebound fraction, f, which is an indicator of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…This trend can be attributed to the higher hygroscopicity of inorganic aerosols compared to that of their organic counterparts., ,, When ALWC/PM 2.5 was <∼0.5, a semisolid phase state was predominant (more than 80% of the total PM 2.5 samples, red symbols in Figure ), whereas when ALWC/PM 2.5 was ≥∼0.5, a liquid phase state was predominant (more than 80% of the total PM 2.5 samples, green symbols in Figure ). A recent study of Qiu et al investigated the relationship between ALWC/PM 1.0 and phase states of aerosol particles. The authors showed that PM 1.0 tended to be a liquid phase state in Beijing when ALWC/PM 1.0 >∼0.3.…”
Section: Resultsmentioning
confidence: 99%
“…This trend can be attributed to the higher hygroscopicity of inorganic aerosols compared to that of their organic counterparts., ,, When ALWC/PM 2.5 was <∼0.5, a semisolid phase state was predominant (more than 80% of the total PM 2.5 samples, red symbols in Figure ), whereas when ALWC/PM 2.5 was ≥∼0.5, a liquid phase state was predominant (more than 80% of the total PM 2.5 samples, green symbols in Figure ). A recent study of Qiu et al investigated the relationship between ALWC/PM 1.0 and phase states of aerosol particles. The authors showed that PM 1.0 tended to be a liquid phase state in Beijing when ALWC/PM 1.0 >∼0.3.…”
Section: Resultsmentioning
confidence: 99%
“…Over the past decade, in China, aerosol phase state has become a focal point in atmospheric aerosol research (Kuang et al, 2016;Y. Liu et al, 2017;Qiu et al, 2023;Sun et al, 2018). These findings collectively suggest that aerosols in ambient air may exist in stable or partially metastable states when the RH of the air is below the critical fully DRH.…”
Section: Introductionmentioning
confidence: 95%
“…The characteristics of ambient aerosols exhibiting deliquescent behavior, along with the corresponding deliquescence relative humidity (DRH) and efflorescence RH (ERH), are influenced by aerosol chemical composition, including the proportions of nitrate (Sun et al., 2018) and secondary organic aerosols (SOA) (Saukko et al., 2015; Wang et al., 2021), as well as other factors such as mixing state (Li et al., 2021; Xiong et al., 2023). Over the past decade, in China, aerosol phase state has become a focal point in atmospheric aerosol research (Kuang et al., 2016; Y. Liu et al., 2017; Qiu et al., 2023; Sun et al., 2018). These findings collectively suggest that aerosols in ambient air may exist in stable or partially metastable states when the RH of the air is below the critical fully DRH.…”
Section: Introductionmentioning
confidence: 99%